Let the Ideological and Moral Education Classroom Quiet -- On the Misunderstandings and Countermeasures in the Open Class of Ideological and Moral Education - Huang, Maorong; Guo, Yaping; Zheng, Qianwen (Journal of Education and Educational Technologies, 2023)
People have created history through continuous evolution, and history is also the carrier of decades of changes in human society. The history of physics, as a key research topic in recent years, has played a crucial role in human exploration of various physical phenomena in nature. The history of physics showcases the process of deduction and calculation behind every physical formula, enabling students to understand that research in physics cannot be achieved overnight, in order to correct their attitude and responsibility towards science. Administrative agreement dispute is a kind of dispute in the process of signing, performing, changing and suspending administrative agreement. Because of the dual nature of administrative agreement, there are different views on the theory and practice of mediation of disputes. To work out the agreement controversy between the administrative theme and the parties to the agreement properly, we should first make clear the administrative attribute of the agreement, and then use the existing feasible means to solve them. The current relief way of administrative agreement disputes is mainly administrative litigation, which can not deal with the increasingly complex administrative agreement disputes. This paper analyzes the shortcomings of the existing ways of administrative agreement dispute relief, expounds the feasibility of a variety of ways of dispute relief, and puts forward some suggestions on the construction and improvement of the relief system of administrative agreement dispute through the construction of two-way litigation method and the redistribution of the responsibility of demonstrate.